Dasar-Dasar Pelaksanaan Pendidikan Agama Islam di Sekolah - Ayatullah, Ayatullah (Lembaga Yasin AlSys, 2022)
Islamic Religious Education as one of the subjects in schools has a very strategic and significant role in the formation of students' character and personality. Islamic education in general can be understood as an effort to increase students' faith, understanding, appreciation and practice of the religion of Islam so that they become Muslim individuals who believe and are pious and have noble character in personal, social, national and state life. The basis of Islamic religious education is of course based on the philosophy of life of Muslims and not based on the philosophy of life, a country, because the Islamic education system can be implemented anywhere and anytime without being limited by space and time. Education is basically a communication process which includes the transformation of knowledge, values and skills inside and outside school that lasts a lifetime, from generation to generation.